Characteristics of Foreign-Born Persons in the Swiss Hepatitis C Cohort Study: Implications for Screening Recommendations. - Barbara Bertisch (PLoS ONE, 2016)
BACKGROUND:Switzerland recommends individuals who originate from high-prevalence countries to be screened for hepatitis C virus (HCV) infection. However, not all these persons are equally at risk. We thus aimed to describe the number and characteristics of persons with HCV infection born outside of Switzerland. METHODS:We compared characteristics of anti-HCV-positive individuals in the Swiss Hepatitis C Cohort Study (SCCS) and of HCV cases reported to the Federal Office of Public Health (FOPH), with those of the general population in Switzerland. Persons who inject drugs (PWID) and persons who do not inject drugs (non-PWID) were compared by age groups for different countries of origin (represented by ≥1% of participants in the SCCS or FOPH). RESULTS:We included 4,199 persons from the SCCS and 26,610 cases from the FOPH. Both groups had similar characteristics. In both data sources non-PWID were more frequent in foreign-born than in Swiss-born persons (63% versus 34% in the SCCS). The only subgroup with a clearly higher proportion both in the SCCS and FOPH than in the general population were persons over 60 years from Italy and Spain, with a 3.7- and 2.8-fold increase in the SCCS. These persons were non-PWID (99%), less frequently HIV- and anti-HBc positive and more often female than PWID from Italy and Spain; cirrhosis at enrolment was frequent (31%). Their HCV genotypes were consistent with those observed in elderly non-PWID of their birth countries. In the FOPH a higher proportion than in the general population was also seen for cases from Georgia and Russia. CONCLUSION:The identification of subgroups in which HCV infection is particularly frequent might allow for better targeting HCV screening among foreign-born persons in Switzerland and elsewhere.